2018
DOI: 10.1007/s12094-018-1845-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic analysis of stage pT1b kidney neoplasms for optimal surgical margins of nephron-sparing surgery

Abstract: ObjectiveTo evaluate the pathological features and define the optimal surgical margins (SM) of nephron-sparing surgery (NSS) for kidney neoplasms 4–7 cm (stage pT1b) on preoperative imaging.Materials and methodsThe retrospective study included 748 patients who were diagnosed stage pT1b renal tumors and underwent either radical nephrectomy (RN, n = 475) or NSS (n = 273) from January 2004 to March 2017. The tumor size, pathological subtype, Fuhrman grade, status of peritumoral pseudocapsule (PC) and tumor multif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is one of the largest meta-analyses evaluating the predictors of PSMs. Traditionally, the occurrence of PSMs after NSS was considered to be related to the nature of the RCC and the surgical procedure (3739). In the current study, PSMs were statistically associated with Furhman grade (3–4 vs. 1–2), pathologic stage (3–4 vs. 1–2), non-ccRCC histology, and non-white race.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is one of the largest meta-analyses evaluating the predictors of PSMs. Traditionally, the occurrence of PSMs after NSS was considered to be related to the nature of the RCC and the surgical procedure (3739). In the current study, PSMs were statistically associated with Furhman grade (3–4 vs. 1–2), pathologic stage (3–4 vs. 1–2), non-ccRCC histology, and non-white race.…”
Section: Discussionmentioning
confidence: 99%
“…5 A prior study found that the rate of tumor seeding and metastasis can be effectively reduced by avoiding tumor incisions. 6 However, accidental tumor incision (ATI) occasionally occurs in patients treated with NSS and is associated with tumor recurrence and metastasis. 7 To investigate the risk factors for tumor recurrence and metastases associated with ATI, we collected data from pT1N0M0 RCC patients who underwent NSS between 2010 and 2015.…”
Section: Introductionmentioning
confidence: 99%